Numerical simulations of fatigue failure processes in intermittent jointed rock masses under the action of repeated stress waves - Ma, Shuyin; Xue, Sheng; Pan, Cheng (Frontiers in Earth Science, 2023)
To study the fatigue failure of an intermittent jointed rock mass under repeated stress waves, numerical models of jointed rock masses with different joint angles were created using Autodyne software, and crack propagation behavior was simulated using the Drucker–Prager strength model and cumulative damage failure criteria. In this numerical simulation, the influence of stress wave amplitude and the mode of disturbance on fatigue failure of the rock mass were analyzed. The simulation results showed a significant difference between the failure process of jointed rock masses subjected to repeated stress waves and those exposed to a single stress wave, including crack initiation locations, propagation paths, and rock mass failure patterns. With increasing angles of inclination, the fatigue life of the rock mass first decreased and then increased under repeated stress waves. As the joint inclination angle, β, increased from 20° to 50°, it had a significant influence on the fatigue life of the rock mass, which decreased rapidly with increases in β. The variation in the disturbance form (the change in amplitude of the stress waves from small to large, or from large to small) did not affect the final macro failure pattern of the rock mass; but the extent of damage to the rock mass was affected.